How Long Did You Look At Me? The Influence of Gaze Direction on Perceived Duration and Temporal Sensitivity. (June 2016) - Thönes, Sven; Hecht, Heiko
Faces that exhibit emotionally negative expressions in mutual gaze have been shown to induce a dilation of perceived duration. The influence of gaze by itself on duration judgments, however, has rarely been investigated. We argue for a social interaction hypothesis, according to which humans should be highly accurate and precise (sensitive) when processing the temporal dynamics of mutual gaze. In three experiments, we investigated whether the direction of observed gaze affects perceived duration and temporal sensitivity. In Experiment 1, subjects did indeed estimate the duration of direct gaze more accurately as compared to the duration of averted gaze. In Experiments 2 and 3, subjects had to categorize direct and averted gaze stimuli as being short or long in duration (temporal bisection). Experiment 2 found temporal sensitivity (but not mean duration judgments) to be improved in cases of mutual gaze. In Experiment 3, the effect of mutual gaze on prolonged subjective duration did replicate, however, it was rather small. Moreover, temporal precision was not improved in the case of naturalistic stimuli. In sum, effects of mutual gaze on duration judgments are rather weak, and cannot be attributed to arousal, as such ratings did not differ between direct and averted gaze stimuli.